Kecerdasan Emosional Tokoh dalam Novel Madogiwa No Totto Chan Karya Tetsuko Kuroyanagi - Hastuti Hastuti; Dian Permanasari (LPPM STKIP PGRI Bandar Lampung, 2025)
This study is a descriptive psychological analysis based on Goleman's theory of emotional intelligence of the character Totto Chan in the novel Madogiwa no Totto Chan by Tetsuko Kuroyanagi. The purpose of this study is to determine the level of emotional intelligence of Totto Chan in the novel Madogiwa no Totto Chan by Tetsuko Kuroyanagi. The results of the analysis in this study show that the character of Totto Chan has seven elements of emotional intelligence. This is demonstrated by her high confidence in success, her constant desire to learn and try new things, her ability to plan well and not give up on her goals, her self-control in adjusting her desires to the demands of her environment, her excellent relationships with others, and her ability to understand their situations and conditions. the main character communicates well, and the main character can work well with others. Therefore, Totto Chan's emotional intelligence is very high.